Orange yield in orchard floor vegetation management - Fidalski, Jonez; Marur, Celso Jamil; Auler, Pedro Antonio Martins; Tormena, Cássio Antonio (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate water status, physiological parameters and fruit yield of the Pear orange on Rangpur lime rootstock, as well as soil water content in different orchard floor vegetation management. Field experiment was set up in 1993, at Alto Paraná, northwest of the state of Paraná, Brazil. The soil is a Typic Paleudults. Three treatments were evaluated: bahiagrass (Paspalum notatum), legume (Arachis pintoi), and spontaneous vegetation plus herbicide. The experimental design was in random blocks with three replicates. From 1999 to 2003, the following measurements were made: photosynthesis rates, stomatal conductance, leaf water potential, fruit yield and soil water content. Legume keeping in the interrows causes higher stress to orange plants. Bahiagrass assures better water and metabolic relations to Pear orange tree. Fruit yield orange is not influenced by orchard floor vegetation management.